Anti –phytopathogenic Activities of Cladophora glomerata extract against plant fungi - Baghdad Science Journal (مجلة بغداد للعلوم, 2014)
The antiphytopathogenic effects of the crude methanol extract of Cladophora glomerata (Lin.) Kützing (Cladophoraceae) which isolated from Al Rashidiya region at north of Baghdad was investigated against two type of plant fungi (Pythium altimum and Rhizoctonia solani) which causes damping off disease where isolated from covered cucumber field in Al-Alyosifia region. Hot methanol extract showed antifungal activity against the two species of fungi in different concentrations(10,25,50 mg/ml) of extract to Cladophora glomerata as percentage inhibition (51.63 ,72.8 ,83.71) and (56.18 ,77.41 ,100)comparing with Pythium altimum and Rhizoctonia solani respectively .primary detection of active compounds showed that macroalgae (Cladophora glomerata) containing flavonoids,alkaloids, phenols and tannins. Our findings suggest the possibility of using the Cladophora glomerata as a novel source of natural antimicrobial agents for pharmaceutical industries.